The Patients Save Lives Program to Facilitate Organ Donor Designation in Primary Care Offices. (September 2019) - Degenholtz, Howard B.; Creppage, Kathleen; DaCosta, Damian; Drozd, Alexandra; Enos, Misty; Himber, Meleah; Lazzara, Kristin; Razdan, Manik; Resnick, Abby; Shaw, Yomei
Background: There are about 120 000 people on the US waiting list for a solid organ transplant; nearly 22 people die every day who could be helped through organ donation. Joining a donor registry and informing one's family of one's preferences increases recovery rates and can avoid misunderstandings during an emotionally difficult time. Although the vast majority of people support organ donation, only about half of adults have joined a state donor registry. Methods. A 3-group design was used. Primary care physician offices were randomly assigned to either web-based training, in-person training, or a control condition. The control condition consisted of a poster and traditional brochure and donor form placed in the waiting room. In the 2 intervention groups, the Patients Save Lives form was distributed during the check-in process in addition to the poster. Results: A total of 1521 physicians and office staff at 81 clinic sites (48 in-person and 33 web-based) received the training; there were 33 control locations. A total of 21 189 patients were exposed to the intervention over a 6-month period; 761 (8.1%) of 9428 people who were not already registered completed the designation form to be organ donors. There were no donor designations in the control group locations. Conclusion: Organ donor designation can be incorporated into the office check-in procedure without disrupting the workflow or burdening clinicians. The program is available online and can be sustained inexpensively with cooperation between primary care offices and regional Organ Procurement Organizations.